Produtividade de variedades de sorgo em diferentes arranjos populacionais em primeiro corte e rebrota - Da Silva, Toshik Iarley; Santana, Laudeline Dantas; Da Camara, Felipe Thomaz [UNESP]; Pinto, Antônio Alves; De Brito, Leonardo Lenin Marques; Mota, Antônio Marcos Duarte (My University, 2017)
The sorghum is a promising alternative for the supplement food human and animal. The objective of this work was to evaluate the production of two cultivars of sorghum with different space arrangements produced in first and second cuts. Was used a randomized block designing in factorial scheme 2 x 3 with three replicates. The datas were submitted to analysis of variance and Tukey test at 5% probability. The BRS Ponta Negra variety was at that showed the best results in the first and in the second cuts. The best arrangement was of two at two plants at every 14 cm.
Yield of varieties of sorghum in different populations arrangments in first cut and regrowth
Keywords: Harvest; Production; Sorghum bicolor; Varieties